2002
DOI: 10.1359/jbmr.2002.17.2.266
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Flow Induction of Cyclo-Oxygenase 2 Gene Expression in Osteoblasts Is Dependent on an Extracellular Signal-Regulated Kinase Signaling Pathway

Abstract: Mechanical loading of bone may be transmitted to osteocytes and osteoblasts via shear stresses at cell surfaces generated by the flow of interstitial fluid. The stimulated production of prostaglandins, which mediates some effects of mechanical loading on bone, is dependent on inducible cyclo-oxygenase 2 (COX-2) in bone cells. We examined the fluid shear stress (FSS) induction of COX-2 gene expression in immortalized MC3T3-E1 osteoblastic cells stably transfected with ؊371/؉70 base pairs (bp) of the COX-2 5-fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
96
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(106 citation statements)
references
References 49 publications
(47 reference statements)
5
96
5
Order By: Relevance
“…at the endothelial cell luminal surface into intracellular signaling events (56,57). The induction of COX-2 by soluble integrin ligands observed in the present study is consistent with the reported induction of COX-2 expression in endothelial cells (58 -60) and osteoblasts (61,62) in response to fluid shear stress. These observations raise the possibility that vascular integrins on tumor endothelial cells may contribute to sustain COX-2 expression in response to increased shear stress due to the pathological architecture of tumor vessels (63) or to increased levels of circulating soluble ECM protein fragment observed in cancer conditions (64,65).…”
Section: Fig 4 Huvec Adhesion To Different Ecm Proteins Induces Coxsupporting
confidence: 91%
“…at the endothelial cell luminal surface into intracellular signaling events (56,57). The induction of COX-2 by soluble integrin ligands observed in the present study is consistent with the reported induction of COX-2 expression in endothelial cells (58 -60) and osteoblasts (61,62) in response to fluid shear stress. These observations raise the possibility that vascular integrins on tumor endothelial cells may contribute to sustain COX-2 expression in response to increased shear stress due to the pathological architecture of tumor vessels (63) or to increased levels of circulating soluble ECM protein fragment observed in cancer conditions (64,65).…”
Section: Fig 4 Huvec Adhesion To Different Ecm Proteins Induces Coxsupporting
confidence: 91%
“…[6][7][8][9][10][11] These results have been found in osteoblastic cell lines, and in primary bone cells from several species including humans. 8,[12][13][14][15][16][17][18][19] Specifically, the production of nitric oxide (NO) and prostaglandins (PG) is stimulated in bone cells in response to fluid flow. 8,[20][21][22][23] Osteocytes are more responsive than osteoblasts, whereas periostial fibroblasts show almost no response.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study, we demonstrated the role of oscillatory flow in the induction of cytosol Ca 2+ release from the ER, and enhancement of mRNA expression of osteopontin (You et al, 2001). Other researchers also showed that flow stimulation on bone cells enhances cyclooxygenase-2 (COX-2) expression, causes activation of the ERK pathway, and leads to ATP release (Wadhwa et al, 2002;Genetos et al, 2007;Okumura et al, 2008). However, long-term constant mechanical loading does not increase the response of bone cells continuously.…”
Section: Introductionmentioning
confidence: 92%